2012
DOI: 10.1507/endocrj.ej11-0193
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of kisspeptin neurons in the rat forebrain with special reference to sexual dimorphism and interaction with GnRH neurons

Abstract: Kisspeptin/metastin has been implicated as a critical regulator in luteinizing hormone (LH) secretion and the reproductive system mediating the effect of estrogen on GnRH neurons. In the present study we examined the sex differences in the effects of estrogen on Kiss1/kisspeptin expression in the forebrain by using gonadectomized rats to assess the interaction of kisspeptin and GnRH neurons. Kiss1/kisspeptin cell bodies were abundant in the rostral periventricular area of the third ventricle (RV3P) and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
(53 reference statements)
8
39
1
Order By: Relevance
“…Our imaging studies found that fluorescently labelled MeA Kiss neurons were concentrated in the MeApd but were also distributed throughout the MeAa and MeApv, whereas previous studies have located Kiss1 mRNA principally in the MeApd of mice [38]. In mice, kisspeptin protein is almost undetectable using conventional immunolabelling techniques, probably due to much lower expression or more rapid release compared to other rodents [38, 39]. However, recent labelling approaches using different transgenic mouse lines have confirmed that Kiss1 gene-driven reporters localize in the MeAa and MeApv [37, 40], supporting our data.…”
Section: Discussionmentioning
confidence: 64%
“…Our imaging studies found that fluorescently labelled MeA Kiss neurons were concentrated in the MeApd but were also distributed throughout the MeAa and MeApv, whereas previous studies have located Kiss1 mRNA principally in the MeApd of mice [38]. In mice, kisspeptin protein is almost undetectable using conventional immunolabelling techniques, probably due to much lower expression or more rapid release compared to other rodents [38, 39]. However, recent labelling approaches using different transgenic mouse lines have confirmed that Kiss1 gene-driven reporters localize in the MeAa and MeApv [37, 40], supporting our data.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand our results contradict findings showing that haloperidol supports the NPY mRNA expression in the rat amygdala (Śmiałowska et al 2001) and increase hypothalamic GnRH and CRF mRNA levels (Park et al 2011; Umathe et al 2009). The changes in Kiss-1 mRNA expression seem to be especially interesting in the context of recent evidence proving an important role of kisspeptin signaling in the physiology of medial amygdala (Di Giorgio et al 2014; Xu et al 2012; Yeo et al 2016). Taking into account that Kiss-1 expression in the amygdala is controlled by circulating sex hormones (Cao and Patisaul 2013; Kim et al 2011), and kisspeptin neurons in MeA are sensitive to the pheromone molecules (Pineda et al 2017), the analogous comparative study on females has to be definitely proven.…”
Section: Resultsmentioning
confidence: 98%
“…The dorsomedial nucleus of the hypothalamus (DMH) contains a small group of kisspeptin cells, demonstrated by ICC using specific antibodies, in mice, guinea pigs, sheep and horses, but these cells are not present in the rat or hamster (Table 3.1). Likewise, there is species variation in the presence of cells in the ventromedial hypothalamic nucleus (VMH), with cells being detected in the sheep (in some reports (32) but not others (33)) and rats (24), but not in other species; as in the case of kisspeptin cells in the median eminence (39), these cells may be an extension of the ARC population, in this case laterally. Regardless, evidence of kisspeptin cells in the DMH and VMH in a number of species rests primarily on ICC data, and additional ISH data would be worthwhile to verify their presence in these species.…”
Section: 2 Distribution Of Kisspeptin and Kiss1 In The Adult Brainmentioning
confidence: 99%